2011
DOI: 10.1002/hbm.21042
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal white matter integrity in young children with autism

Abstract: This study investigated white matter integrity in young children with autism using diffusion tensor imaging (DTI). Twenty-two children with autism, mean age 3:2 years, and 32 controls, mean age 3:4 years, participated in the study. Tract-based spatial statistics (TBSS) revealed white matter abnormalities in several distinct clusters within the genu and body of the corpus callosum (CC), left superior longitudinal fasciculus (SLF) and right and left cingulum (Cg). TBSS-VOIs analysis was performed in the clusters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
187
2
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(216 citation statements)
references
References 66 publications
22
187
2
2
Order By: Relevance
“…In regard to weaknesses on tasks measuring attentional control, working memory, and cognitive processing and response speed, the NF1 IQ profile is in keeping with research on other developmental disabilities, showing a consistent susceptibility to disruption in attention, working memory, and cognitive efficiency functions (Oliveras-Rentas et al 2011;Mayes and Calhoun 2006). These types of neuropsychological deficits are linked to disruptions in white matter tracts, which are particularly vulnerable due to their protracted developmental trajectory (e.g., Barnea-Goraly et al 2005) and are commonly seen in developmental disabilities including NF1, ADHD, and autism spectrum disorders (ASD) (e.g., Lawrence et al 2013;Weinstein et al 2011;Cutting et al 2002). From this perspective, the IQ profile seen in children with NF1 reflects similar vulnerabilities as those observed in other developmental disabilities, such as ADHD and ASD.…”
Section: Impairment Levelssupporting
confidence: 73%
“…In regard to weaknesses on tasks measuring attentional control, working memory, and cognitive processing and response speed, the NF1 IQ profile is in keeping with research on other developmental disabilities, showing a consistent susceptibility to disruption in attention, working memory, and cognitive efficiency functions (Oliveras-Rentas et al 2011;Mayes and Calhoun 2006). These types of neuropsychological deficits are linked to disruptions in white matter tracts, which are particularly vulnerable due to their protracted developmental trajectory (e.g., Barnea-Goraly et al 2005) and are commonly seen in developmental disabilities including NF1, ADHD, and autism spectrum disorders (ASD) (e.g., Lawrence et al 2013;Weinstein et al 2011;Cutting et al 2002). From this perspective, the IQ profile seen in children with NF1 reflects similar vulnerabilities as those observed in other developmental disabilities, such as ADHD and ASD.…”
Section: Impairment Levelssupporting
confidence: 73%
“…6,7,[25][26][27][28][29][30][31][32] Lee et al 33 also demonstrated an increase in MD in the bilateral white matter of the superior temporal gyrus and right temporal stem in patients with high-functioning autism compared with age-matched TD. The authors also found an overall reduction in , 2 , 3 and attributed the findings along these pathways, critically involved in language and social cognition, to microstructural disorganization.…”
Section: Discussionmentioning
confidence: 93%
“…Ten studies gathered imaging data while some participants were under general anesthesia and an additional two while participants were sleeping naturally, presumably reducing head motion. Of these studies, however, only one imaged both ASD and typical groups under anesthesia (21). Indeed, one study that imaged participants with ASD under anesthesia and typical participants while asleep concluded that at least some of their group differences were likely caused by differences in motion (22).…”
Section: Discussionmentioning
confidence: 99%